2019
DOI: 10.1016/j.psyneuen.2019.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Null results of oxytocin and vasopressin administration across a range of social cognitive and behavioral paradigms: Evidence from a randomized controlled trial

Abstract: Research examining oxytocin and vasopressin in humans has the potential to elucidate neurobiological mechanisms underlying human sociality that have been previously unknown or not well characterized. A primary goal of this work is to increase our knowledge about neurodevelopmental and psychiatric disorders characterized by impairments in social cognition. However, years of research highlighting wide-ranging effects of, in particular, intranasal oxytocin administration have been tempered as the fields of psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 37 publications
(66 reference statements)
1
28
0
Order By: Relevance
“…The great majority of studies emphasize positive, prosocial behavioral outcomes after exogenous oxytocin administration; however, it is important to emphasize that not all studies describe these effects (Keech et al, 2018 ; Tabak et al, 2019 ; Erdozain and Peñagarikano, 2020 ) and some antisocial outcomes have been reported, including increased competitive and aggressive tendencies, particularly in males (Fischer-Shofty et al, 2012 ; Alcorn et al, 2015 ; Ne’eman et al, 2016 ; de Jong and Neumann, 2018 ; Gedeon et al, 2019 ). Others have also reported differential effects of exogenous oxytocin on women compared to men (e.g., Rilling et al, 2012 , 2018 ; Preckel et al, 2014 ; Feng et al, 2015 ; Chen et al, 2016 ; Bredewold and Veenema, 2018 ; Bartz et al, 2019 ; Xu et al, 2020 ).…”
Section: Oxytocin In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…The great majority of studies emphasize positive, prosocial behavioral outcomes after exogenous oxytocin administration; however, it is important to emphasize that not all studies describe these effects (Keech et al, 2018 ; Tabak et al, 2019 ; Erdozain and Peñagarikano, 2020 ) and some antisocial outcomes have been reported, including increased competitive and aggressive tendencies, particularly in males (Fischer-Shofty et al, 2012 ; Alcorn et al, 2015 ; Ne’eman et al, 2016 ; de Jong and Neumann, 2018 ; Gedeon et al, 2019 ). Others have also reported differential effects of exogenous oxytocin on women compared to men (e.g., Rilling et al, 2012 , 2018 ; Preckel et al, 2014 ; Feng et al, 2015 ; Chen et al, 2016 ; Bredewold and Veenema, 2018 ; Bartz et al, 2019 ; Xu et al, 2020 ).…”
Section: Oxytocin In Humansmentioning
confidence: 99%
“…AVP is also thought to influence human behavior in many ways (Neumann and Landgraf, 2012 ; Benarroch, 2013 ) although significant effects are not always evident (Tabak et al, 2019 ). AVP and oxytocin may interact with each other to influence prosocial vs. antisocial behaviors, trust vs. aggression, fear and so on (Huber et al, 2005 ; Veenema and Neumann, 2018 ; Ebstein et al, 2012 ; Rilling et al, 2012 ; Jurek and Neumann, 2018 ; Song and Albers, 2018 ; Berends et al, 2019 ), at least some of which are sexually dimorphic (Rilling et al, 2014 ; Feng et al, 2015 ; Bredewold and Veenema, 2018 ).…”
Section: The Links Between Oxytocin and Musicmentioning
confidence: 99%
“…We limited this analysis to EMG responses to happy faces, as our task failed to elicit mimicry of anger. Given that there is no clear theoretical boundary for oxytocin's social-cognitive effects for setting the equivalence bounds (Quintana, 2018), we defined the smallest effect size of interest-based on the smallest effect size detectable with 80% power given our sample size (Quintana, 2018;Tabak et al, 2019). The alpha level was set to 0.05.…”
Section: Equivalence Testingmentioning
confidence: 99%
“…Avpr1a encodes a receptor for arginine vasopressin, which is a neurohypophysial hormone involved in the regulation of adrenocorticotropic hormone released from the pituitary 44 . A recent study has shown that the blocking AVPR1A may improve social communication in autism spectrum disorder 45 . Chat encodes an enzyme which catalyzes the biosynthesis of the neurotransmitter acetylcholine.…”
Section: Hypothalamus Datamentioning
confidence: 99%